A comparative computational and experimental study of Al–ZrO2 thin films for optoelectronic applications. (15th December 2022) - Zeeshan, Talat; Qureshi, Muhammad Tauseef; Kayani, Zohra Nazir; Arshad, Amara; Ullah, Farman; Hameed, Reda Abdel; Ragab, Hanan; Alam, Noor; Rehman, Wajid; Saleem, Murtaza
Abstract: Modern optoelectronic devices are highly dependent upon the electronic and optical characteristics of semiconducting materials. In this work, pure and Al-doped ZrO2 compositions were studied comparatively studied using simulations and experimental investigations. The uniform and well-distributed granular thin films were experimentally deposited. X-ray diffraction analysis reveals the tetragonal crystal structure with the space group 137 P4_2/nmc. The density of states predicts the p-d hybridization in ZrO2 and presents overlapping of Al-states at the Fermi level in Al-containing compositions. Band structure was deduced using generalized gradient approximations that were found to reduce with the increment of Al content in the structure. The absorption coefficient increases with an increase in Al content in the low energy region and redshift is noticed attributed to the inter-band absorption in semiconductors. The experimentally calculated energy band gap value decreases from 2.76 eV for ZrO2 to 1.80 eV for the maximum content of Al composition. Highlights: First principal investigations on Pure and Al-doped ZrO2 . Density of states predicts the p-d hybridization in ZrO2. Growth of uniform granular thin films. Structural analysis reveals the tetragonal crystal structure. Band gap values decreased from 2.76 eV to 1.80 eV.